Patients with Sjogren's Syndrome and Depression Who Got MenometrorraghiaAfter Receiving Antidepressant - Ines Damayanti Octaviani (Indonesian Rheumatology Associantion, 2025)
Background: Sjogren's Syndrome (SS) is a systemic autoimmune diseasethat attacks the mucous glands and other organs of the body. SS can alsomanifest in neuropsychiatric forms such as fatigue, depression, andanxiety. Case presentation: Whether the menometrorrhagia that occurs inSS patients who has depression is caused by the disease or caused by theadministration of antidepressant and which antidepressant is appropriatefor patient. The method is by searching for scientific evidence throughtrusted databases, such as PubMEd, Cochrane, Scholar, Springer andMedscape using The Boolean Operator method using keywords with filtersfor journal publications in the last 15 years, human research subjects andEnglish language. There were 6 studies that matched the clinical question.Conclusion: There is an evidence that meno/metrorrhagia in SS patientscan be caused by the disease itself and the antidepressant that were taking.It preferable to be substituted the antidepressants with less bleedingincidence such as Clomipramine, Fluvoxamine, and Mirtazapine.